Peningkatan Kemampuan Motorik Kasar pada Anak Usia 4-5 Tahun Melalui Permainan Lompat Tali - Wahid, Santi M.J.; Marasabesy, Anwar (Lembaga Bale Literasi, 2024)
This research aims to determine the increase in gross motor skills in children aged 4-5 years through jumping rope games at PAUD Sarpisa Center Kec. North Galela. This research is Classroom Action Research (collaborative) which consists of two cycles and four meetings. The researcher acts as a teacher who carries out the learning scenario, while the collaborator is an assistant class teacher who acts as an observer. The research subjects were 9 children in class A PAUD Sarpisa Center, consisting of 4 boys and 5 girls. Data collection techniques are observation and field notes. The research instrument used an observation sheet in the form of a check list of children's gross motor skills. The collected data was analyzed descriptively qualitatively and quantitatively. The results of this research show that there is an increase in children's gross motor skills through the jump rope game at PAUD Sarpisa Center. The increase in children's gross motor skills in cycle I was 55.5% or 5 children out of 9 children were in the criteria of very good, good, strong and balanced, there was an increase in cycle II, namely 88.9% or 8 children out of 9 children were in the criteria of very good and is good for strength and balance. Thus, the jump rope game can improve gross motor skills in children aged 4-5 years at PAUD Sarpisa Center Kec. North Galela.